Preferensi Konsumen terhadap Sifat Organoleptik dan HargaTelur Asin Original dan Oregano (Plectanthrus amboinicus SPRENG) - Sundari, Ristina Siti; Fitriadi, Budhi Wahyu; Hidayati, Reny (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2025)
Eggs are functional foods that are always available in every home, considering their nutritional content and practicality of serving. However, duck eggs are still constrained in consumption because of their sharp, eggy smell. This study aims to determine consumer preferences for the organoleptic properties of original and oregano-salted eggs (Plectanthrus amboinicus SPRENG). Data were obtained through an organoleptic test questionnaire to 85 respondents. Data analysis used an independent sample t-test. The results showed that original and oregano-salted eggs had the same preferences for the color of the egg yolk and egg white. The texture of oregano-salted eggs differs from that of the original salted eggs. The taste of egg yolk and egg white differs greatly from original salted eggs and oregano salted eggs. Oregano-salted eggs have a better taste than oregano-salted eggs. The most prominent difference is that the aroma of oregano-salted eggs no longer smells eggy. It is very preferred by consumers.